ANALYSIS OF THE STATE OF THE HACCP SYSTEM IN THE DAIRY INDUSTRY IN RNM - Kalevska, Tatjana; Kosteska, Marina; Martinovski, Sasko; Stamatovska, Viktorija; Nikolovska Nedelkoska, Daniela (Horizons - International Scientific Journal, 2021)
The HACCP food safety system is a preventive approach to the analysis and control of hazards at all stages of food production, which is a legal obligation for all food operators, including the dairy industry. The purpose of this paper is to analyze the state of the HACCP system in the Macedonian dairies and to identify the factors that affect its functioning. The survey covered 16 dairies with different structure and capacity. The obtained data shows that all dairies without exception have implemented and apply the HACCP system, of which only 62.5% have certified it. As one of the benefits of the application of the HACCP system, 87.5% of the dairies point out the product safety improvement and the increased trust of the consumers, for which all the dairies answered in the affirmative. Food premises requirements, financial resources and insufficient staff education are some of the problems in implementing the HACCP system that most dairies have faced.